PENGARUH STRUKTUR KEPEMILIKAN SAHAM TERHADAP TRANSAKSI PADA PIHAK YANG MEMPUNYAI HUBUNGAN ISTIMEWA - Dyah Puspasari; Imam Subekti; Endang Mardiati (El Dinar, 2015)
Abstract The objective of this study is to investigate the effect of ownership structure to the related party transaction and board directors’s compensation practice as moderating variable. This study uses managerial ownership, financial institution ownership, family ownership, government ownership, and public ownership as proxy of ownership structures and related party transaction (RPT) asset, liabilities, purchase, and sales as proxy of related party transaction (RPT). This research used 152 non financial companies listed in Indonesia Stock Exchange by using purposive sampling. The result of this study show that family ownership, managerial ownership have positive effects on RPT Asset, Liabilities, Purchase, and Sales. Whereas financial institution ownership and public ownership have negative effects on RPT Asset, Liabilities, Purchase, and Sales. Whereas government ownership not significant on RPT Asset, Liabilities, Purchase, and Sales. Results of other examination show that board director’s compensation will strengthen managerial ownership’ effect to the RPT Asset, Liabilities, Purchase, and Sales.